Efficacy of Stream Sediment Survey in delineating geochemical halos: A case study of well and non-shed areas in the Gambe-Tola Baryte District, Northeastern Nigeria - Halilu, Maimuna (IJRDO-Journal of Applied Science, 2017)
The efficacy of stream sediment survey in delineating geochemical halos is assessed in the Gambe-Tola Area of Northeastern Nigeria. Well-shed area had a higher statistical probability of being associated with geochemical halos synonymous with elevated concentrations in the rocks whereas less shed shed areas sometimes showed little or no correlation to elevated concentrations in the rocks. Efforts to trace known Baryte mineralization in the area through geochemical halos from stream sediment was unsuccessful as the mineralized areas were not well shed, due to large dispersion distance at sampling and natural solubility of BaSo4 in water.